Knowledge, Attitudes, and Behaviors Towards HIV-AIDS Prevention (Descriptive Study in Harapan Village, Kwamki Narama District, Mimika Regency - Central Papua) - Nursinah Nursinah; Muslimin B (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This research is motivated by the increasing cases of HIV/AIDS in Indonesia due to a lack of knowledge, information, and public awareness about HIV/AIDS. In addition, social prejudice and discrimination still exist. Therefore, it is considered necessary to make maximum effort to prevent it. Changes in human behavior are expected to reduce the rate of spread of HIV/AIDS in society because it can hinder socio-economic development and threaten national stability. The purpose of this study was to describe HIV/AIDS prevention efforts in Harapan Village, Kwamki Narama District, Mimika Regency, Papua. The type of research used was research with a descriptive research design to obtain a detailed description of HIV/AIDS prevention behavior. The number of samples is 80 with a simple random sampling method. As a result, the percentage of respondents who took appropriate HIV/AIDS prevention measures was the highest at 66.3%, followed by appropriate attitudes at 63.8% and knowledge of appropriate attitudes at 53.8%, followed by %. This means that there is a significant relationship between behavior and attitudes towards behavior in HIV/AIDS prevention. There is no significant relationship between knowledge and action in HIV/AIDS prevention. It was concluded that respondents' lack of knowledge influences their behavior in preventing HIV/AIDS. In terms of attitude, the behavior of respondents who take or do not avoid HIV/AIDS transmission can influence their behavior in the decision-making process as well as their behavior in HIV/AIDS prevention. The bottom line is that knowledge, attitudes, and actions are very important in efforts to combat HIV/AIDS